Changes in Volatile Profiles and Activity of Hydroperoxide Lyase and Alcohol Dehydrogenase During the Development of Cabernet Sauvignon Grapes (Vitis vinifera L.) - OuYang, Ya Nan’; Shan Gao, Jin; Lan Li, Ruo; Rong Zhu, Mei; Hao Hu, Xin; Min, Zhuo; Chen, Shu Xia; Zhang, Zhen Wen; Fang, Yu Lin (South African Journal of Enology and Viticulture, 2016)
In this study we focused on the development of Cabernet Sauvignon grapes and investigated changes in the activity of alcohol dehydrogenase (ADH) and hydroperoxide lyase (HPL) in different tissues. We sampled grape skin at four, six, seven, eight, nine, 10, 12, 14 and 16 weeks after anthesis; developing flowers when blooming at 0%, 5%, 50%, and 90%; and leaves at two and four weeks before anthesis and at two, four, six, eight, nine, and 10 weeks after anthesis. We also examined the type and fluctuation of volatile contents. ADH activity increased with the development of flowers and grape skins, which led to the increasing of types and concentration of alcohols. Low levels of 9-HPL led to low concentrations of C9 compounds. According to this paper, C6 compounds became abundant with the development of grape berries, while the activity of 13-HPL kept at a low level in the flowers and grape skins. There might have been a high level of 13-HPL activity from the end of flowering until fruit setting that we did not detect. Furthermore, similar C6 and C5 compounds were detected across all tissues, including hexanal, (E)-2-hexenal, (Z)-3-hexenal, (Z)-2-penten-1-ol, (Z)-3-hexen-1-ol, 1-hexanol and 3-hexen-1-ol. Generally speaking, the concentrations of C6 and C5 compounds could be used as the criterion of maturation of the three grape tissues.